THE ROLE OF MILLETS IN ATTAINING SUSTAINABLE DEVELOPMENT GOALS. - Gogoi, Buli (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Millets are the highly nutritious ancient grains. Consumption of millets as staple diet can supply superior nutrients and combat malnutrition. The small-sized grain holds promise for addressing food security to ever increasing population. These helps to prevent lifestyle related chronic diseases. The climate-resilient crops require no pesticides and fertilizers. The drought-resistant, resilient, short-growing, cost-effective crops can bring a positive transformation in agriculture. Climate change, uncertainty of weather can be sustainably addressed by promoting millets. The plant millets can convert more Carbon-Dioxide to Oxygen and reduce the carbon footprints of agriculture up to 30%. Cultivation and consumption of millets is the best way to maintain the balance on health, soil, water, and air. It can play a key role to bring back diversity in food grains for healthy, disease free life as well as sustainable future. In this paper an attempt has been made to highlight the unique characteristics and potentialities of millets in achieving Sustainable Development Goals-1. No poverty, 2. Zero hunger, 3. Health and Well-being, 6. Water and Sanitation, 8. Decent work and Economic growth, 11. Sustainable cities and communities, 12 Responsible consumption and production. 13. Climate Actions.